HOME INDUSTRY INTIP MARKETING REACH OF SUMBERLAWANG DISTRICT VILLAGE, SRAGEN DISTRICT - Rafiani, Minda; Rahman, MS Khabibur; Rifa’i, Muh. Husyain (Universitas Veteran Bangun Nusantara, 2019)
The Marketing Range of Intip Home Industries at Jati Village Sumberlawang Sub-District Sragen Regency in 2018. Geography Education Program, Teacher Training and Education Faculty, Veteran Bangun Nusantara University, Sukohar. 2020.This study aims to determine the distribution of Intip Home Industry in Jati Village Sumberlawang Subdistrict Sragen Regency, to determine the effect of its marketing range on economic conditions and to know the labor’s income of the Intip Home Industry in Sendangrejo Village Sumberlawang District, Sragen Regency. The method used in this study is Saturated Sampling Method which is the determination of the sample if all members of the population are used as samples. It is often done if the population is relatively small, less than 30 people, or the study wants to generalize with small errors. Another term of this method is a census, where all members of the population are sampled. Starting from this, the study included saturated samples because there were fewer than 30 people. The results of this study can be concluded that domestic marketing includes Pati, Jepara, Blora, Tuban, Mantingan, Jogja, Solo, Sragen, Boyolali, Wonogiri, Purwodadi, Demak, Kudus, Klaten, Delanggu, Ngawi, and Kartasura. The economic condition of the workforce in the home industry is relatively low, which is less than Rp. 1,000,000 every month. The majority of dependents in worker’s family is categorized as medium class with around 3-5 dependents for each family. The duration of their business is between 10-15 years.